The pivotal role of dysregulated autophagy in the progression of non-alcoholic fatty liver disease - Shen, Qiaohui; Yang, Ming; Wang, Song; Chen, Xingyu; Chen, Sulan; Zhang, Rui; Xiong, Zhuang; Leng, Yan (Frontiers in Endocrinology, 2024)
Non-alcoholic fatty liver disease (NAFLD) is a clinicopathologic syndrome characterized by excessive fat deposition in hepatocytes and a major cause of end-stage liver disease. Autophagy is a metabolic pathway responsible for degrading cytoplasmic products and damaged organelles, playing a pivotal role in maintaining the homeostasis and functionality of hepatocytes. Recent studies have shown that pharmacological intervention to activate or restore autophagy provides benefits for liver function recovery by promoting the clearance of lipid droplets (LDs) in hepatocytes, decreasing the production of pro-inflammatory factors, and inhibiting activated hepatic stellate cells (HSCs), thus improving liver fibrosis and slowing down the progression of NAFLD. This article summarizes the physiological process of autophagy, elucidates the close relationship between NAFLD and autophagy, and discusses the effects of drugs on autophagy and signaling pathways from the perspectives of hepatocytes, kupffer cells (KCs), and HSCs to provide assistance in the clinical management of NAFLD.